2019
DOI: 10.31871/ijntr.5.7.6
|View full text |Cite
|
Sign up to set email alerts
|

Ask the Assistant: Using Google Assistant in Classroom Reading Comprehension Activities

Abstract: Language education is ever evolving to accommodate changes brought about by time and the development and breakthroughs in the education sector in general, and to rectify or improve non-effective approaches to suit unique language learning needs that may arise. This research was carried out to investigate the use of Google Assistant to help a group of rural primary learners in Baram, Sarawak, Malaysia who struggled with reading comprehension activities. There are two main objectives outlined for this study. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…When it is used as an educational tool, it might have some pernicious effects, if misused. In case of ethical and moral issues, its use for educational purposes may turn out to be perilous with its disadvantages, and hence it is advisable that these tools be used under supervision (Sing et al, 2019).…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…When it is used as an educational tool, it might have some pernicious effects, if misused. In case of ethical and moral issues, its use for educational purposes may turn out to be perilous with its disadvantages, and hence it is advisable that these tools be used under supervision (Sing et al, 2019).…”
Section: Empirical Backgroundmentioning
confidence: 99%
“…They stated that utilizing GA to practice English speaking and listening was less stressful than other in-class activities like speaking in front of their teachers and classmates. According to Sing et al (2019), GA is a reasonably useful tool according to three measurable criteria: the number of questions posed, the number of questions accurately answered, and the amount of time needed to do comprehension tests. Additionally, the use of Google Assistant has had a distinguishable positive impact on respondents' perceptions of the reading comprehension task itself (Sing et al, 2019).…”
Section: Google Assistant Is An Effective Tool For Listening Speaking...mentioning
confidence: 99%
“…According to Sing et al (2019), GA is a reasonably useful tool according to three measurable criteria: the number of questions posed, the number of questions accurately answered, and the amount of time needed to do comprehension tests. Additionally, the use of Google Assistant has had a distinguishable positive impact on respondents' perceptions of the reading comprehension task itself (Sing et al, 2019). From the above experimental studies, it is evident that GA is an effective tool for learning listening, speaking, and reading skills.…”
Section: Google Assistant Is An Effective Tool For Listening Speaking...mentioning
confidence: 99%
“…In another research [28] aimed to study the effectiveness of voice assistants, and specifically Google Assistant in language learning, data collected from a sample of 10 students in a Malaysia area, showed that Google Assistant is a functional tool that can be applied in teaching and especially in language learning.…”
Section: Voice Assistants As Language Learning Toolsmentioning
confidence: 99%